ANALYSIS OF THE INFLUENCE OF THE PRINCIPAL'S LEADERSHIP STYLE ON TEACHER PERFORMANCE AT SDN 2 BENCAH, SELATAN BANGKA DISTRICT - Sukma, Odi; Hidayati, Dian (Universitas Pendidikan Indonesia, 2024)
This study aims to describe the headmaster’s leadership style and the factors that affect the leadership behavior of the headmaster at the State Elementary School 2 Bencah, South Bangka Regency. This study was descriptive qualitative research. The subjects in this study were the headmaster, teachers of grade I (one) to grade VI (six), several students in grade V (five), and students in grade VI (six). The data collection techniques used in this study were observation and interviews. The data were analyzed using data reduction, data display, and concluding—the data validity test techniques used by source triangulation. The results of the study showed that the leadership style used by the headmaster at the State Elementary School 2 Bencah tends to the democratic, aggressive leadership style. It can see from the way the headmaster solving problems and making decisions, which is always carrying out by arranging meetings, discussions, and forums with staff and teachers. However, the headmaster also always gives punishment to undisciplined teachers and rewards for outstanding teachers.